Effect of aging type and aged unit on the repair strength of resin composite to feldspathic porcelain in testing microtensile bond strength - Corazza, Pedro Henrique; Carvalho, Rodrigo Furtado De [UNESP]; Souza, Rodrigo Othávio De Assunção E; Bottino, Marco Antonio [UNESP]; Özcan, Mutlu (Taylor & Francis, 2016)
The aim of the present study is to investigate the effect of aging type (thermocycling vs. water storage) and aged unit (block vs. stick) on the repair strength of resin composite to feldspathic porcelain in testing microtensile bond strength (TBS). Ceramic specimens (N = 30) (10 × 5.7 × 4.5 mm3, Vita Mark II, Vita) were obtained from CAD-CAM blocks. One surface was etched with 10% HF and silanized. An adhesive was applied and resin composite blocks were constructed incrementally on the conditioned surface. The specimens were randomly divided into five groups (n = 6): Control (C): Non-aged; BTC: Blocks were thermocycled (5-55 °C, 6000 cycles); STC: Sticks were thermocycled; BS: Blocks aged in water storage (6 months) after themocycling; SS: Blocks aged in water storage (6 months) after thermocycling. After TBS test, failure types were classified. Data (MPa) were statistically analyzed (1-way and Dunett and 2-way ANOVA, Tukey's) (α = 0.05). Two-parameter Weibull distribution values including the Weibull modulus, scale (m), and shape (0) values were calculated. Aging type (p = 0.009) and aged unit (p = 0.000) significantly affected the results. Interaction terms were also significant (p = 0.000). Considering the stick level, there was no significant difference between thermocycling (STC: 25.7 ± 2.3) and water storage (SS: 25.3 ± 3.8) (p > 0.05) but the results were significantly higher when blocks were thermocycled (BTC: 31.6 ± 2.9) (p < 0.05). Weibull modulus and characteristic strength was the highest in BTC (m = 4.2; σo: 34.4) among all other groups (m = 3-3.9; σo: 14.6-28.5). Adhesive failures were common and cohesive failures occurred in less than 5% in all groups. Aging protocol was detrimental on durability of repair strength of resin composite to feldspathic porcelain. Exposing the sticks to either thermocycling or water storage aging should be considered in in vitro studies.
Keywords: adhesion; aging; bond strength; repair; resin composite